A Formative Qualitative Evaluation to Inform Implementation of a Research Participation Enhancement and Advocacy Training Program for Diverse Seniors: The DREAMS Program. (July 2019) - Perkins, Molly M.; Hart, Ariel; Dillard, Rebecca L.; Wincek, Ronald C.; Jones, David E.; Hackney, Madeleine E.
This article reports on a formative qualitative evaluation conducted to identify potential barriers and facilitators prior to implementation of a two-part educational intervention designed to increase older adults' participation in clinical research. We conducted focus groups with 35 older adults from diverse racial, ethnic, and socioeconomic backgrounds (Mean age = 74.5 ± 7.4 years), and six clinical researchers involved in aging research. Two older adult patient stakeholder advisors participated as members of the research team. Findings from thematic analysis showed that common barriers to research participation included older adults' fear and mistrust of researchers and the medical community as well as misperceptions and negative attitudes about clinical research. A commonly held belief was that most clinical research is conducted by "greedy" pharmaceutical companies who are more interested in profits than finding cures for disease. Results provide useful insights regarding enrolling members of hard-to-reach older adult populations in clinical research.